STUDI ANALISA INDEK KEPUASAN MAHASISWA PRODI PENDIDIKAN TEKNOLOGI INFORMASI UIN AR-RANIRY - Bustami Yusuf (UIN Ar-Raniry, 2018)
The purpose of this study aims to analyze student satisfaction of Information Technology Education (ITE) Department, Faculty of Tarbiyah and Teacher Training, Ar-Raniry State Islamic University. The respondent are used all active students of ITE Department (N=460). This research uses quantitative, descriptive, and comparative method with Anova Test analysis based on lecturer, lecture, and year of class. The results of this study indicate that there are significant differences in student satisfaction either based on teaching lecturers (F=9,72, P>0.05), the courses taken (F = 6.639, p>0.05), or based on year of class(F=11.855, P>0.05). This research contributes as an initial evaluation material for department of ITE to improve the quality of student services.